Every day in Tuscany : seasons of an Italian life - Mayes, Frances (Broadway Books, 2010)
In this sequel to her" New York Times" bestsellers" Under the Tuscan Sun" and" Bella Tuscany," the celebrated "bard of Tuscany" ("New York Times") Frances Mayes lyrically chronicles her continuing, two decades-long love affair with Tuscany's people, art, cuisine, and lifestyle.